Traditional Production of Siratany in Ranomay and conservation Issues in the Amoron'i Onilahy Protected Area, Southwest Region of Madagascar - Norodiny; Raharinirina Tolojanahary Lucianne Nicole; Defemur Zafiry Velontahina Zafiry; Rodine Manena Bylla; Reveka Mampitohy Fialia; Réné de Rolland Lily-Arison (Ite Ngabdi, 2026)
This study aims to evaluate the traditional production of siratany in Ranomay and its implications for biodiversity conservation within the Amoron'i Onilahy Protected Area in southwestern Madagascar. Specifically, it describes the traditional production process and assesses its biological, physical, and socio-economic impacts. A mixed-methods case study approach was employed, integrating field observations, semi-structured interviews, household surveys, and a focus group discussion with 40 respondents comprising production workers, kettle owners, fuelwood sellers, and members of VOI TSIFA. Quantitative data were analyzed using descriptive statistics, while qualitative information was examined through thematic analysis. The results revealed that siratany production remains a family-based activity founded on indigenous knowledge transmitted across generations and consists of four major stages: preparation, brine filtration, combustion, and drying. Each production cycle consumes approximately 60 L of water and an average of 15 pieces of fuelwood per kettle, indicating substantial dependence on local natural resources. The activity provides an important source of household income and supports local markets, thereby contributing to rural livelihoods and the preservation of cultural heritage. However, increasing fuelwood demand and reliance on traditional wood-fired combustion may intensify pressure on dry forest ecosystems and pose environmental and health concerns if resource use is not sustainably managed. Community-based conservation initiatives led by VOI TSIFA, including reforestation and environmental awareness activities, demonstrate the potential for integrating traditional livelihoods with biodiversity conservation, although institutional and resource limitations remain. The study concludes that improving fuelwood management, promoting energy-efficient production technologies, strengthening community participation, and enhancing the market value of siratany are essential to ensuring the long-term sustainability of this traditional industry while supporting the conservation objectives of the Amoron'i Onilahy Protected Area.